Análise Dialógica De Maria Da Vila Matilde: A Canção No Embate Contra A Violência De Gênero (PERcursos Linguísticos, 2020)
This work analyses Douglas Germano’s song “Maria da Vila Matilde”, sung by Elza Soares, from the perspective of the dialogical discourse theory. In a moment such as this, in which the feminist discourse is strengthening (in part, due to the social medias), and the fight against chauvinism is growing, the artistic discourse can contribute to strengthen an empowering attitude towards the confrontation of such questions. In the song analysis, we can observe which social values and discursive categories constitute a domestic violence denunciation discourse.  Elza Soares’ singing of the song is analyzed in its ironic key in order to observe how this discursive category can establish several tinctures which create, axiologically, the confrontational tone of the female lyrical voice against chauvinist values.